Applying the L3 assessment framework to identify knowledge gaps on the impact of classroom activities and listening on children’s learning and wellbeing - Kiri Mealings; Joerg M. Buchholz (Discover Education)
Abstract The Listen to Learn for Life Assessment Framework outlines how to systematically assess the links between the classroom environment, listening, learning, and wellbeing. The aims of this paper were to (i) understand what is known and what is not known about how the characterised activity impacts primary school children’s learning and wellbeing, and (ii) understand what is known and what is not known about how hearing, listening, comprehending, and communicating (Functioning Assessment) impacts primary school children’s learning and wellbeing. Literature reviews were conducted to address both of these aims. The most researched aspects of the characterised activity were background noise, SNRs, and reverberation, with the results showing that poor acoustic conditions have negative effects on children’s learning and wellbeing (though the number of studies on wellbeing was limited). However, there were many aspects of the characterised activity that have not yet been explored, and there were also areas of learning and wellbeing that need to be examined in future research. The only link that was found between the spectrum of listening and learning or wellbeing was between listening comprehension and reading comprehension, with children who have better listening comprehension having better reading comprehension. Overall, this review revealed the importance of creating an environment that is optimised for children’s listening, learning, and wellbeing. However, future research is still needed to understand exactly what the environments need to be across different characterised activities to ensure all aspects of children’s learning and wellbeing are optimised.